2017
DOI: 10.3390/f8060185
|View full text |Cite
|
Sign up to set email alerts
|

Seed Origin and Protection Are Important Factors Affecting Post-Fire Initial Recruitment in Pine Forest Areas

Abstract: Abstract:Initial seedling recruitment is one of the most critical stages for plants in the Mediterranean basin. Moreover, wildfires and post-fire environmental conditions might deteriorate regeneration success, which can lead to problems for sustainable forest restoration and forest persistence. On this context, different seed origins and pine species may be better adapted to new environmental conditions remaining after forest fires and seed protection might modulate seedling initial recruitment. This study ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The height of the seedlings in the last year of investigation was statistically inferior in Bistrit , a-Năsăud provenance. The small height compared with the other provenances may have been due either to consanguinity among the seedlings, or could have been influenced by the origin of the seeds, which may have been collected from other trees that were not correctly selected or were genetically debilitated [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…The height of the seedlings in the last year of investigation was statistically inferior in Bistrit , a-Năsăud provenance. The small height compared with the other provenances may have been due either to consanguinity among the seedlings, or could have been influenced by the origin of the seeds, which may have been collected from other trees that were not correctly selected or were genetically debilitated [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, both strategies could be implemented. Sources of information include ecological descriptions, site maps, list of species, historical and current photographs, biological studies and paleoecology [26].…”
Section: Ecological Restorationmentioning
confidence: 99%
“…Based on the available data, the recurrence of large wildfires is threatening the conservation of P. nigra ecosystems, as very little natural regeneration occurs in these species' forests after wildfires. Because the black pine is a non-serotinous pine, and because it has no adaptive mechanisms to crown fires, the natural regeneration of the species is limited to a short distance from the unburnt stands [3,10,12]. Seed dispersal models have shown that the natural regeneration of the black pine occurs at distances no greater than 100 m, depending on the following factors: the side seeding potential, site characteristics (soil fertility, moisture, slope, etc.…”
Section: Introductionmentioning
confidence: 99%